Pendekatan Holistik Evaluasi Pembelajaran dan Implikasinya dalam Bimbingan dan Konseling - Nur Annisa Sawitri; Juwita Madira; Ghina Rizki Amalia; Saniya Putri Ayu Febiolantika; Minarsi Minarsi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the function of the scientific approach and learning assessment as elements that strengthen the quality of education through a structured literature review. The review of various sources shows that the continuous application of the scientific method has a positive effect on improving students’ critical thinking, creativity, learning independence, and character development. Findings from several studies over the past decade support the effectiveness of implementing the scientific method at various educational levels, despite challenges such as limited time and learning resources. In addition, comprehensive learning evaluation not only measures final outcomes but also considers context, input, and process (CIPP model), thereby enhancing the relevance of learning objectives and student motivation. The literature review also highlights the importance of guidance and counseling (GC) as an integrative component that supports students’ academic, social, personal, and character development at both primary and secondary education levels. However, some studies identify challenges in implementation, such as students’ low reading interest and the dominant role of teachers, which can be addressed through STEM-based and blended learning models. Overall, the integration of GC with learning evaluation has the potential to realize holistic education that balances intellectual, emotional, social, moral, and spiritual intelligence, while preparing students to contribute effectively to society and the future workforce. These findings encourage the development of educational policies and learning practices that are more process-oriented, context-based, and focused on the holistic development of student competencies.